Історія дослідження виробів з виїмчастими емалями київської культури - Abrazumova, Olena M. (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2024)
The article analyses the history of research and study of jewellery production by the people of the Middle and Upper Dnieper region in the late Roman period. One of the most recognizable products of the area and time in question are ornaments with carved enamels. The first attempts to understand them started over a century ago. During the first half of the 20th century, the ethnocultural affiliation of the circle of carved enamel decorations was debatable. With the selection of Kyiv culture (the indicated original products of applied art being among the signs thereof), another dimension is added to the study of enamelled jewellery. Modern archaeologists have not tired of the chronology, cataloguing and classification, technological, the artistic and stylistic aspects of the production of jewellery and metal parts of clothing of the Kyiv culture, or attempts at understanding of the phenomenon of recessed enamels. The rapid growth of the finds of jewellery and elements of clothing with carved enamels has led to another perception of their distribution and habitation, and the origins of the style of the jewellery of Kyiv masters.